Isotherm of ammonia adsorption on zeolite CaA (MSS-622) - Ergashev , Oybek; Bazarbaev, Muratali; Juraeva, Ziyoda; Bakhronov, Khayot; Kokharov, Mirzokhid; Mamadaliyev, Utkurbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the experimentally obtained values of the adsorption isotherm of ammonia molecules on zeolitite СаА (MSS-622) at a temperature of 303 K. The isotherm was measured using a DAC-1-1A microcalorimeter connected to a universal high-vacuum device. The relationship between the amount of ammonia adsorption and its energetic characteristics on СаА (MSS-622) zeolite was established. Additionally, the sorption mechanism from the initial adsorption stage to the experimental range and the filling behavior of ammonia molecules in the zeolite's volume were determined. Under experimental conditions, the adsorption capacity of this zeolite for ammonia was found to be 10.2 mmol/g per gram of zeolite. It was determined that 43% of the total adsorption occurs at an equilibrium pressure of 0.33 torr, 53% at 1.4 torr, 71% at 25 torr, 80% at 200 torr, 98% at 476 torr, and 100% at 614 torr. The adsorption isotherm was reinterpreted using the three-term equation of the volumetric filling theory of micropores (VMOT), and the theoretically calculated values were shown to fully match the experimental data. It was proven that ammonia molecules initially form tetrameric ion-molecular complexes 4NH3:Na+ with sodium cations and subsequently trimeric complexes 3NH3:Ca2+ with calcium cations in the first coordination sphere of the zeolite.